Effect of the Y : B ratio on phase purity and development of thermally stable nano-sized Eu+3-doped YBO3 red phosphor using sodium borohydride1. Issue 17 (7th May 2015) - Srivastava, Shubham; Behera, Shantanu K.; Nayak, Bibhuti B.
<x xml:space="preserve">Abstract</x> A borohydride derived thermally stable nano-sized Eu3+-doped YBO3 red phosphor is described.